Integrating Character Education in English Learning to Develop Student Character in Senior High School - Jihan Aldie Fathani; Sholihatul Hamidah Daulay (Didaktika: Jurnal Kependidikan, 2025)
This study explores the integration of character education into academic programs as a strategy to promote holistic student development. Through approaches such as experiential learning, role modeling, community service, and the cultivation of a positive school culture, core values—including respect, responsibility, empathy, integrity, and resilience—can be effectively instilled. Findings indicate that character education positively impacts academic achievement, reduces behavioral issues, and fosters the development of emotionally intelligent and socially responsible individuals. However, implementation faces challenges such as aligning academic and character goals, preparing educators, and adapting to diverse cultural contexts. The study highlights the importance of collaboration among schools, families, and communities in designing sustainable character education programs that are relevant to the demands of a globalized society.